Numerical investigations of dynamic stall on a rotor with cyclic pitch control - Letzgus, J.; Gardner, A.D.; Schwermer, T.; Kessler, M.; Krämer, E. (My University, 2017)
Numerical investigations of three-dimensional dynamic stall on a two-bladed Mach-scaled rotor (R = 0.65m, Ma75 = 0.21, Re75 = 3.5 × 105) with 1/rev cyclic pitch control are presented and compared to experimental surface pressure and PIV data. In addition to URANS simulations using the finite-volume flow solvers FLOWer and TAU, a delayed detached-eddy simulation (DDES) with Menter SST as underlying RANS model is carried out with FLOWer. Facing dynamic stall and flow separation, the DDES reproduces high-frequency load fluctuations, cycle-to-cycle variations and small-scale vortical structures as seen in the experiment, which is not the case with URANS. However, common hybrid RANS-LES issues – grid-induced separation and the grey area problem – play a role in this DDES and influence loads severely. FLOWer SST simulations yield load peaks of the same magnitude as individual, non-phase-averaged measurements. With TAU SST the dynamic stall event is delayed and weakened compared to FLOWer SST and experimental results. FLOWer and TAU results using the SA turbulence model are fairly comparable but in bad agreement with the experiment at the outboard station at r/R = 0.77, where they exhibit no dynamic stall at all.